3D AMR hydrosimulations of a compact-source scenario for the Galactic Centre cloud G2. Issue 4 (1st June 2018) - Ballone, A; Schartmann, M; Burkert, A; Gillessen, S; Plewa, P M; Genzel, R; Pfuhl, O; Eisenhauer, F; Habibi, M; Ott, T; George, E M
ABSTRACT: The nature of the gaseous and dusty cloud G2 in the Galactic Centre is still under debate. We present three-dimensional hydrodynamical adaptive mesh refinement simulations of G2, modelled as an outflow from a 'compact source' moving on the observed orbit. The construction of mock position-velocity (PV) diagrams enables a direct comparison with observations and allows us to conclude that the observational properties of the gaseous component of G2 could be matched by a massive (M_w=5× 10^-7 M_ yr^-1 ) and slow (50 km s −1 ) outflow, as observed for T Tauri stars. In order for this to be true, only the material at larger (>100 AU) distances from the source must be actually emitting; otherwise G2 would appear too compact compared to the observed PV diagrams. On the other hand, the presence of a central dusty source might be able to explain the compactness of G2's dust component. In the present scenario, 5–10 years after pericentre the compact source should decouple from the previously ejected material, due to the hydrodynamic interaction of the latter with the surrounding hot and dense atmosphere. In this case, a new outflow should form, ahead of the previous one, which would be the smoking gun evidence for an outflow scenario.